Damage development during flexural loading of a 5-directional braided C/C-SiC composite, characterized by X-ray tomography and digital volume correlation. Issue 5 (1st April 2019) - Wan, Fan; Liu, Rongjun; Wang, Yanfei; Cao, Yingbin; Zhang, Changrui; Marrow, Thomas James
Abstract: In situ observations of damage development within 3-dimensional 5-directional braided carbon fiber reinforced carbon and silicon carbide (C/C-SiC) ceramic composites, fabricated by gaseous silicon infiltration (GSI) and precursor infiltration pyrolysis (PIP), have been obtained using laboratory X-ray computed tomography during in situ flexural tests. The GSI composite has a denser structure than that fabricated by PIP, but contains initial defects within the fiber bundles. The GSI composite ultimately failed due to fracture across the fiber bundles, while failure of the higher strength PIP composite propagated along the interface between the fiber bundle and matrix with a greater degree of fiber pullout. These differences arise from the higher process temperature and greater degree of matrix-fiber reaction of GSI compared to PIP. Digital volume correlation (DVC), applied to the tomographs, measured the 3-dimensional deformations and hence the specimen curvature. This demonstrated the significant reduction in elastic modulus caused by the development of internal cracking with tensile strain in both materials.